Pola Aliran Air Tanah Pada Desa Panteriek Lueng Bata Kota Banda Aceh - Eva Herlina; Mery Silviana (Center for Research and Community Service (LPPM) University of Abulyatama, 2020)
The village of Panteriek, one of the villages in the municipality of Banda Aceh, experienced a change in groundwater quality commonly used for daily living needs. Decreasing groundwater quality can be caused by poor community sewerage systems, WC production, septic tanks and absorbing wells that do not meet the requirements of both quality and layout of pollutants. The purpose of this research is to give data about the problems that happened to groundwater quality in research area. In this research, the aspects studied are ground water resource potential in research area, ground water usage pattern and to get contour of ground water flow direction used flownet system. Based on the dug well distribution map and cross-sectional well-water river system based on the groundwater depth data of each well following the flow pattern of groundwater-oxbow-river water in the study area is the groundwater flow pattern that is oxbow filling ground water and other ground water side fill the river water.